2021
DOI: 10.1016/j.jaac.2020.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Population Prevalence of the Posttraumatic Stress Disorder Subtype for Young Children in Nationwide Surveys of the British General Population and of Children in Care

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…As a result of the findings from Study 1 showing that PTSD-YC identifies children with PTSD up to age 8 years who are missed by the standard PTSD diagnosis alongside the other similar data that prompted the age cutoff in Study 1 (Danzi & La Greca, 2017;Hitchcock et al, 2021;Meiser-Stedman et al, 2008), and in accordance with the slightly wider age range recruited in some prior CBT trials providing treatment to young children experiencing PTSD (e.g. Salloum et al, 2016), we recruited young children with PTSD-YC up to 8 years of age.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As a result of the findings from Study 1 showing that PTSD-YC identifies children with PTSD up to age 8 years who are missed by the standard PTSD diagnosis alongside the other similar data that prompted the age cutoff in Study 1 (Danzi & La Greca, 2017;Hitchcock et al, 2021;Meiser-Stedman et al, 2008), and in accordance with the slightly wider age range recruited in some prior CBT trials providing treatment to young children experiencing PTSD (e.g. Salloum et al, 2016), we recruited young children with PTSD-YC up to 8 years of age.…”
Section: Discussionmentioning
confidence: 94%
“…Previous research has suggested that the PTSD‐YC diagnosis may be a more appropriate conceptualization of PTSD beyond the preschool range for children up to 8 years of age (Danzi & La Greca, 2017; Hitchcock et al., 2021; Meiser‐Stedman et al., 2008). For this reason, the present study also reports prevalence estimates for children both up to 6 years and up to 8 years.…”
Section: Study 1: Dsm‐5 Acute Stress Disorder and Ptsd‐yc In Trauma Exposed Young Children Following Emergency Room Attendancementioning
confidence: 99%
“…Although not without criticism ( 31 ), the DSM-5 added two new criteria as part of the new symptom cluster D of negative cognitions and mood: “Persistent, distorted cognitions about the cause or consequences of the traumatic event(s) that lead the individual to blame himself/herself or others” (p. 4), as well as “persistent negative emotional state (e.g., fear, horror, anger, guilt, or shame)” (p. 3). In trauma-exposed foster children, aged 5 to 8, PTSD diagnosis rates were 54% of children ( 32 ). Among juvenile detainees, CSA predicted PTSD symptoms, over and above other forms of trauma ( 17 ), suggesting unique impact of CSA.…”
Section: Csa Post-traumatic Stress and The Selfmentioning
confidence: 99%
“…anxiety, depression) are also highly prevalent and associated with childhood adversity in autistic youth (Kerns, Newschaffer, Berkowitz, & Lee, 2017;Kerns, Rast, & Shattuck, 2020). By contrast, rates of post-traumatic stress disorder (PTSD) appear similar to or less than that seen in the general pediatric population (Hitchcock et al, 2021;Hoch & Youssef, 2020;Kerns, Newschaffer, & Berkowitz, 2015). This is surprising given many features related to ASD, such as social disconnection, intellectual disability, anxiety, and emotion dysregulation increase the risk for developing PTSD following a potentially traumatic event (Kerns et al, 2015).…”
Section: Introductionmentioning
confidence: 99%